Enhancing Law Enforcement Efficiency: A Comparative Study of Manual and Biometrics Systems in PSP - Francisco, Guimarães; Pedro , Moita; Sonia M. A., Morgado (Magyar Rendészet, 2025)
The urgent need for technological modernisation in law enforcement, particularly to combat cybercrime and enhance IT security, is evident. Current manual procedures are increasingly questioned regarding efficiency compared to advanced technologies like biometrics and AI, which are widely used elsewhere. This study evaluates the time, cost and security benefits of biometric sensors versus manual data entry. The methodology is post-positivist with an applied, explanatory approach using quantitative descriptive and inferential statistics. A post-positivist, applied and explanatory methodology, using quantitative descriptive and inferential statistics, was employed. Results from 175 records show that biometric sensors reduce data entry time to 13 minutes, compared to 8 hours and 21 minutes manually. Officers strongly support these technologies. Data from 2023 shows that 89% of 6,113 repeated item merges involve personal identification, highlighting the efficiency of automation. Biometric inputs improve data accuracy, essential for timely legal processes. The findings also reveal higher state expenditures on manual procedures, underscoring the need for technological investments to optimise resources. These results advocate for increased funding to modernise law enforcement, emphasising AI and biometrics as critical for enhancing operational efficiency and decision-making in combating cybercrime and securing IT systems.